Ultrasound Evaluation In Temporomandibular Arthritis In Patients With Chronic Juvenile Arthritis - Iordache Cristina; Ancuta Codrina; Iordache O.; Ancuta E.; Pirlia Carmen; Zenaida Surlari; Chirieac Rodica (Romanian Journal of Oral Rehabilitation, 2011)
The EULAR classification defines the CJA as a systemic manifestation affecting both sexes before 16 years old and registers 3 clinical forms: the systemic disease (Still‘s disease), oligo- and poly-articular. Ultrasonography has remarkable contribution in the diagnosis of musculoskeletal apparatus‘ lesions. Due to the advantages (non-invasive, low cost, no negative effects and contraindications), this method allows the static and dynamic evaluation of the hard and soft structures. The purpose of the paper: to assess TMJ involvement in CJA patients by ultrasonography and to define characteristic patterns of the disease. Material and method: the research was conducted on 2 patients with CJA, hospitalized in Rheumatology Department, Rehabilitation Hospital of Iasi during 01.01.2005-31.07.2006. Assessment was done according to a standard protocol in all patients and included: inflammatory and immune parameters and a complex, both static and dynamic, ultrasound evaluation of TMJ. Descriptive statistical analysis was done using SPSS-11. Results and discussions 86.36% patients featured either inflammatory-destructive or degenerative types ultrasound lesions, the majority of them (59.09%) being inflammatory and destructive. Conclusions a non-invasive, easy, low cost and easily reproducible method, ultrasonography, reconfirmed its diagnostic function in the small joints evaluation, including TMJ.